Equity research apple inc - Pinheiro, António Maria Roquette Eça (2021)
In this part, I did a company overview, where I detailed the share holders structure and Business Structure. Regarding the Business Structure Apple divides itself by region and by product. For the revenue analysis, I used our value drivers to estimate our future revenues, and I also took into consideration components like population, GDP and Market size. In the detail of the regions, I briefly describe devery region. Following that, I talked about the main trends not only regarding the products and Apple it self, but also about some macroeconomics trends. In the end of every region, I came up with a value, that based on my research, I believe is the appropriate to compute in or valuation model. Regarding the products, I did the same as in the regions but I also took a deep dive into the products history, components, competitors, trends, and established to added value input to compute in our valuation model.